The self-esteem and work motivation of Romanian employees in the Covid-19 - Enache, Rodica; Sandu, Mihaela Luminița; Miloș (Ilie), Constаntinа Alinа; Știrbețiu (Stancu) , Maria (Technium Social Sciences Journal, 2021)
The paper entitled The self-esteem and work motivation of romanian employees in the Covid-19 pandemic started from the interest in the field of work psychology and human resources management, seeking to find out the correlational aspects between work motivation and self-esteem amongst public and private employees in Romania. The purpose of the paper was to establish a diagnosis and suggest strategies to improve the existing situation by implementing programs dedicated to motivational stimulation and assessing their impact in other addressed fields